THE RELATIONSHIP OF STUDENTS’ PERCEPTION TOWARD MATHEMATICS SUBJECT AND LEARNING MOTIVATION WITH MATHEMATICS LEARNING ACHIEVEMENT IN CLASS VIII - Fanny Cyintia Dewi; Sunaryo Sunaryo (Universitas Ahmad Dahlan, 2018)
Many factors can influence the results of mathematics learning. Students' perceptions toward mathematics subject and learning motivation are some factors that are suspected of his relationship with the student's mathematics achievement. This study aims to determine whether there is any positive and significant relationship between students' perception of mathematics subject and learning motivation with mathematics learning achievement in class VIII of even semester Muhammadiyah Junior High School 9 Yogyakarta(SMP Muhammadiyah 9 Yogyakarta) academic year 2016/2017. This study population is all students in class VIII of even semester SMP Muhammadiyah 9 Yogyakarta academic year 2016/2017, which consists of 5 classes with a total of 165 students. The sampling class is using a random sampling technique so that obtained class VIIIC amounted to 34 students. The data collecting technique is using the questionnaire method and the test method. Test the instrument using validity test, differentiation power test, and reliability test. Test prerequisite analysis using tests of normality, independent test, and linearity test. Data analysis using regression analysis and correlation analysis. The results of this study indicate a positive and significant relationship between students' perception of mathematics and learning motivation with the mathematics achievement of students with dan so obtained Multiple correlation coefficient (R) = 0,429 with coefficient of determination (R2) = 0,184 with linear regression equation . The relative contribution of (X1) = 31,897%, relative contribution of (X2) = 68,103%, effective contribution of (X1) = 5,867%, and effective contribution of (X2) = 12,526%.